Adoption of immunotherapy in the community for patients diagnosed with metastatic melanoma. Issue 1 (7th November 2019) - Krimphove, Marieke J.; Tully, Karl H.; Friedlander, David F.; Marchese, Maya; Ravi, Praful; Lipsitz, Stuart R.; Kilbridge, Kerry L.; Kibel, Adam S.; Kluth, Luis A.; Ott, Patrick A.; Choueiri, Toni K.; Trinh, Quoc-Dien
Abstract : Background: The introduction of immune checkpoint inhibitors has led to a survival benefit in patients with advanced melanoma; however data on the adoption of immunotherapy in the community are scarce. Methods: Using the National Cancer Database, we identified 4725 patients aged ≥20 diagnosed with metastatic melanoma in the United States between 2011 and 2015. Multinomial regression was used to identify factors associated with the receipt of treatment at a low vs. high immunotherapy prescribing hospital, defined as the bottom and top quintile of hospitals according to their proportion of treating metastatic melanoma patients with immunotherapy. Results: We identified 246 unique hospitals treating patients with metastatic melanoma. Between 2011 and 2015, the proportion of hospitals treating at least 20% of melanoma patients with immunotherapy within 90 days of diagnosis increased from 14.5 to 37.7%. The mean proportion of patients receiving immunotherapy was 7.8% (95% Confidence Interval [CI] 7.47–8.08) and 50.9% (95%-CI 47.6–54.3) in low and high prescribing hospitals, respectively. Predictors of receiving care in a low prescribing hospital included underinsurance (no insurance: relative risk ratio [RRR] 2.44, 95%-CI 1.28–4.67, p  = 0.007; Medicaid: RRR 2.10, 95%-CI 1.12–3.92, p  = 0.020), care in urban areas (RRR 2.58, 95%-CI 1.34–4.96, p  = 0.005) and care at non-academic facilities (RRR 5.18, 95%CI 1.69–15.88, p  = 0.004). Conclusion: While the use of immunotherapy for metastatic melanoma has increased over time, adoption varies widely across hospitals. Underinsured patients were more likely to receive treatment at low immunotherapy prescribing hospitals. The variation suggests inequity in access to these potentially life-saving drugs.